Electroencephalographic analysis in soman‐exposed 21‐day‐old rats and the effects of midazolam or LY293558 with caramiphen. Issue 1 (31st March 2020) - De Araujo Furtado, Marcio; Aroniadou‐Anderjaska, Vassiliki; Figueiredo, Taiza H.; Apland, James P.; Braga, Maria F. M.
Abstract: Acute nerve agent exposure induces status epilepticus (SE), which can cause brain damage or death. Research aiming at developing effective therapies for controlling nerve agent–induced SE is commonly performed in adult rats. The characteristics of nerve agent–induced SE in young rats are less clear; relevant knowledge is necessary for developing effective pediatric therapies. Here, we have used electroencephalographic (EEG) recordings and analysis to study seizures in postnatal day 21 rats exposed to 1.2 × LD50 of soman, and compared the antiseizure efficacy of midazolam (MDZ)—currently considered by the Food and Drug Administration to replace diazepam for treating SE in victims of nerve agent exposure—with that of LY293558, an AMPA/GluK1 receptor antagonist, administered in combination with caramiphen, an antimuscarinic with N ‐methyl‐d ‐aspartate receptor antagonistic properties. Prolonged SE developed in 80% of the rats and was reflected in behavioral seizures/convulsions. Both MDZ and LY293558 + caramiphen stopped the SE induced by soman, but there was a significant recurrence of seizures within 24 h postexposure only in the MDZ‐treated group, as revealed in the raw EEG data and their representation in the frequency domain using a fast Fourier transform and in spectral analysis over 24 hours. In contrast to the high efficacy of LY293558 + caramiphen, MDZ is not an effective treatment for SE induced by soman in young animals. Abstract : The present study showed that the majority (80%) of P21 rats exposed to 1.2 × LD50 soman develop prolonged status epilepticus (SE). Treatment with either MDZ or LY293558 + CRM stopped the initial SE. However, within the 24‐h period postexposure, there was a significant recurrence of seizures in the MDZ‐treated group, while in the LY293558 + CRM–treated group, recurrence of seizures was minimal, and was accompanied by 100% survival rate.